PERAN KESBANGPOL LINMAS DALAM PEMBINAAN ORGANISASI SOSIAL POLITIK DAN ORGANISASI KEMASYARAKATAN - Efyanti, Yasni (Pusat Penelitian dan Pegabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2018)
Abstract: Development in the socio-political field and stabilization of political awareness of life are necessary for every citizen, in order to achieve Pancasila Democracy so that it can guarantee the smooth running of the business to achieve the national goals. This research uses a practical juridical approach. The data obtained will then be analyzed qualitatively by drawing conclusions using inductive methods. The results of this study include: 1) the efforts made by KESBANGPOL LINMAS Sungai Penuh City to maintain political stability in the field of social politics is to provide guidance to existing community organizations, such training is carried out through training in the field of political social. Whereas for social and political power organizations, guidance in the implementation of elections is conducted by conducting scale meetings twice a year to administrators of social political organizations, helping to solve problems faced by these organizations in facing general elections and helping to hold operational facilities.